The association of MTHFR (rs1801133) with hypertension in an indigenous south African population - Mabhida, Sihle E.; Sharma, Jyoti R.; Apalata, Teke; Masilela, Charity; Nomatshila, Sibusiso; Mabasa, Lawrence; Fokkens, Hannah; Benjeddou, Mongi; Muhamed, Babu; Shabalala, Samukelisiwe; Johnson, Rabia (Frontiers in Genetics, 2022)
The current study sought to investigate the association between the methylenetetrahydrofolate reductase (MTHFR) variant (rs1801133) and the risk of developing hypertension (HTN) and further establish a potential link of selected risk factors in an indigenous South African population from Mthatha, Eastern Cape. A total of 442 participants from the indigenous tribe residing in Mthatha, Eastern Cape (South Africa) were recruited. The genotyping of rs1801133 was assessed using MassARRAY® System. Thereafter, the association between rs1801133 in various genetic models and HTN was determined by logistic regression model analysis. Furthermore, the interaction between rs1801133 and selected risk factors on HTN was performed using the open-source MDR The low frequency of the T allele (5%) was also observed when compared with the C allele (95%) in both cases and controls. No significant associations were observed between rs1801133 and the risk of HTN in all genetic models: genotypic (OR 0.75, 95% CI 0.29 - 1.95, p = 0.56), dominant (OR 0.86, 95% CI 0.35 - 2.16, p = 0.75), co-dominant (OR 1.33, 95% CI 0.51 - 3.48, p = 0.55) and allelic (OR 0.80, 95% CI 0.49 - 1.62, p = 0.70) in logistic regression analysis. However, a significant interaction was reported among rs1801133, age, and sex (p <0.0001) with the risk of HTN. The present study demonstrated that there is no significant association between rs1801133 with the risk of HTN in an indigenous South African tribe in our study cohort. However, an interaction between the sex, age, and rs1801133 was observed.